Beneficial Microbes in Fermented and Functional Foods - Rai, V Ravishankar (CRC Press, 2015)
In recent years, fermented and functional foods have seen an incredible increase in consumption due to their potential health benefits. The advances in the field of food technology with the prospective applications of microorganisms and their metabolites have increased the opportunities to develop natural substances as food and food ingredients in fermented and functional foods...